MEMODERASIKAH PERTUMBUHAN EKONOMI TERHADAP BELANJA MODAL? (Studi Kasus Pada Pemerintah Kabupaten/Kota di Provinsi Jawa Tengah Periode 2012-2016) - Devi Inanta Purwati, Mohklas (Stability: Journal of Management and Business, 2019)
AbstrakTujuan penelitian ini untuk mengetahui dan menganalisis pengaruh PAD, DAU, dan DAK terhadap Belanja Modal yang dimoderasi dengan Pertumbuhan Ekonomi. Implikasi manajerialnya adalah sebagai sumbang saran dalam konsep secara ilmiah bagi Pemerinta Daerah /Kabupaten Kota di Jawa Tengah, khusus dalam bidang ilmu akuntansi sektor publik dalam menentukan kebijakan belanja modal.Variabel dalam penelitian ini terdiri dari 5 (lima) variabel dimana pada PAD, DAU dan DAK menjadi variabel bebas sedangkan BM variabel terikat, sedangkan PE sebagai variabel moderat. Teknik populasi dan sampel, seluruh Kabupaten/Kota di Provinsi Jawa Tengah, dengan mengggunakan metode sampling jenuh, jumlah sampel: 175 data. Data penelitian ini berupa data sekunder yang berupa Laporan Realisasi APBD dan tabel PDRB provinsi Jawa Tengah tahun 2012- 2016. Data yang telah dikumpulkan dianalisis pengujian hipotesis dengan uji Moderated Regression Analysis (MRA).Hasil penelitain ini memberikan bukti bahwa; PAD, DAU dan DAK  berpengaruh positif dan signifikan terhadap belanja modal. PE tidak memoderasi  hubungan antara PAD, DAU namun dapat memoderasi DAK dengan BM.Kata Kunci:Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokas Khusus, Belanja Modal, Pertumbuhan Ekonomi  AbstractCapital expenditure has an important role for the Regional Government, with the existence of the Capital Expenditures the Regional Government can improve public services and allocate them to the main objectives; welfare of the community. One of the efforts is; by optimizing the potential for PAD, so the proportion of Capital Expenditures is considered productive. Optimizing the receipt of PAD should be supported, pursued by regional governments by improving the quality of public services. PAD is one component of the source of state financial revenues in addition to other revenues, which can be in the form of; DAU and DAK.Regional autonomy is required to be more independent in managing the household budget, by being more independent in managing its economic resources which will add PAD. But the central government also continues to support local governments through DAU and DAK funds.In general, this study aims to test, analyze the influence of PAD, DAU and DAK on the BM of Regency / City Governments in Central Java with the PE variable dimederator. So that it can be seen whether PE can moderate in influencing BM. In particular, this study aims to provide input from District / City Governments in Central Java, in allocating PAD, DAU and DAK to BM.The variables in this study consist of 5 (five) variables where in PAD, DAU and DAK are independent variables while BM is the dependent variable, while PE is a moderate variable.Population and sample techniques, all regencies / cities in Central Java Province, using saturated sampling methods, number of samples: 175 data. This research data is in the form of secondary data in the form of APBD Realization Report and provincial Central Java GRDP table in 2012-2016. The collected data is analyzed first by testing the classical assumptions then testing the hypotheses using the Moderated Regression Analysis (MRA) test.Keywords: Regional Original Revenue, General Allocation Funds, Special Alokas Funds, Capital Expenditures, Economic Growth